Development of professional competence of bachelors of advertising and public relations - Halyna Horbenko (Інтегровані комунікації, 2016)
In accordance with the bachelor education program of advertising and public relations at the Borys Grinchenko Kyiv University the graduates are meant for mastering the competencies aimed at implementing organizational, managerial, project-oriented, communication, advertising-information, market research and forecasting- analytical activities. It is the competence approach, based on “the culture of professional self-positioning, professional identity, namely formation of the ability to self-determination, self-actualization, self-realization, self-evaluation and self-development", that grows now in widespread popularity in formal education systems. Moreover, the competence approach is the methodological basis for the process of professional identification of the students in higher education institutions, as the higher education reform enters a new phase characterized by the increased attention to development of ideas of a competent approach aimed at developing the state education standards of the third generation.